Viral Bronchiolitis is Associated With Altered Cytokine Gene Expression and Lymphocyte Activation Status. Issue 11 (November 2016) - Leahy, T. Ronan; McManus, Ross; Doherty, Derek G.; Grealy, Robert; Carr, Michael J.; Slattery, Dubhfeasa; Ryan, Thomas
Abstract : Background: Disease severity in viral bronchiolitis is often difficult to predict at onset, and may be related to the host immune response. Recognizing the particular immunologic features of infants who develop severe disease might offer an opportunity for developing diagnostic tools to facilitate early intervention and improve outcomes. Methods: We compared cytokine gene expression (by real-time reverse-transcriptase polymerase chain reaction), cytokine concentrations (by enzyme-linked immunosorbent assay) and the activation status of lymphocytes (by flow cytometry) in the peripheral blood of children hospitalized with moderate and severe viral bronchiolitis and a group of age-matched controls. Results: Analysis was undertaken on 57 children with viral bronchiolitis and 33 controls. Interleukin-7 mRNA expression at enrollment in peripheral blood mononuclear cells differed significantly between those with moderate and severe bronchiolitis, and correlated with both the subsequent length of hospital stay and need for supplemental oxygen therapy. Serum interleukin-10 concentration also distinguished moderate from severe disease. Participants with viral bronchiolitis demonstrated a more activated γδ-T cell phenotype (Vδ 1+), but a more naive TCR αβ-T cell compartment compared with controls. Conclusions: Viral bronchiolitis is characterized by a distinct pattern of cytokine expression and lymphocyte activation. These changes suggest an inadequate innate response in severe disease, and may offer potential as markers of disease severity. Abstract : Supplemental Digital Content is available in the text.